2019
DOI: 10.1016/j.adolescence.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

On the potential harmful effects of E‐Cigarettes (EC) on the developing brain: The relationship between vaping‐induced oxidative stress and adolescent/young adults social maladjustment.

Abstract: Introduction: Evidence suggests that in convenience stores across the United States (U.S), sales of e-cigarettes (EC) continue to grow, indicating their rising popularity. ECs have been touted as a means for traditional cigarette (TC) smokers to quit smoking. However, the dramatic increase in the number of adolescents and young adults using e-cigarettes (vaping) in America is a cause for concern as their long-term effects remain unknown. Methods: Search was done by accessing PubMed/Medline, EBSCO, and PsycINFO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 152 publications
(149 reference statements)
1
66
0
2
Order By: Relevance
“…Exposure to hypoxia, from altitude, smoking, or ENDS, was associated with increased suicides in 9,620,944 people with 22,403 suicides 91 . ENDS have a similar or greater risk relative to conventional cigarettes, causing high levels of intermittent hypoxic stress even without nicotine 93 . Intermittent hypoxia may interact with nicotine in susceptibility to nicotine dependence, possibly through impaired serotonin synthesis, 93 working synergistically with direct effects of nicotine on serotonergic function 36 .…”
Section: Results: Epidemiology and Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to hypoxia, from altitude, smoking, or ENDS, was associated with increased suicides in 9,620,944 people with 22,403 suicides 91 . ENDS have a similar or greater risk relative to conventional cigarettes, causing high levels of intermittent hypoxic stress even without nicotine 93 . Intermittent hypoxia may interact with nicotine in susceptibility to nicotine dependence, possibly through impaired serotonin synthesis, 93 working synergistically with direct effects of nicotine on serotonergic function 36 .…”
Section: Results: Epidemiology and Pharmacologymentioning
confidence: 99%
“…ENDS have a similar or greater risk relative to conventional cigarettes, causing high levels of intermittent hypoxic stress even without nicotine 93 . Intermittent hypoxia may interact with nicotine in susceptibility to nicotine dependence, possibly through impaired serotonin synthesis, 93 working synergistically with direct effects of nicotine on serotonergic function 36 . Children with obstructive sleep apnea are susceptible to impulsive behavior 94 ; young adults with impulsivity and polysubstance abuse have reduced cerebral oxygenation 95 .…”
Section: Results: Epidemiology and Pharmacologymentioning
confidence: 99%
“…One study concluded that both the nicotine and non-nicotine components of e-cigarettes led to increased aggressiveness, impulsiveness, attention deficits, and suicidal ideation among its young users. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…The increase in free radicals and depletion of antioxidants can result in oxidant/antioxidant imbalance, thus augmented oxidative stress. Few studies, however, examined the effect of tobacco consumption (Kahraman, Torun, Osmanoglu, Oruclu, & Ozer, 2017;Tobore, 2019) on oxidative stress among adolescents, with none using Wp. Greater total antioxidant status and total oxidant status, and lower paraoxonase-1 were found in adolescent passive Cg (Kahraman et al, 2017) and e-cigarettes (Tobore, 2019) smokers.…”
mentioning
confidence: 99%
“…Few studies, however, examined the effect of tobacco consumption (Kahraman, Torun, Osmanoglu, Oruclu, & Ozer, 2017;Tobore, 2019) on oxidative stress among adolescents, with none using Wp. Greater total antioxidant status and total oxidant status, and lower paraoxonase-1 were found in adolescent passive Cg (Kahraman et al, 2017) and e-cigarettes (Tobore, 2019) smokers. This increase in oxidative stress was related to number of cigarette exposure (Yildirim, Sermetow, Aycicek, Kocyigit, & Erel, 2011) and resulted in DNA damage of the peripheral blood lymphocytes (Shermatov et al, 2012).…”
mentioning
confidence: 99%